Mapping fast food competitors / Ahmad Imran Oslan - Oslan, Ahmad Imran (2021)
In recent years the creation of maps have advance along with the help of new developed software and technology that is able to collect spatial information from the comfort of their home. These technologies have created new path to creating different types of maps with details that varies according to their user’s needs. Custom maps are high in demands among the marketing franchise as they help them to acquire spatial information and assist them in gathering knowledge to make the most suitable decision to place an establishment in the perfect location. From analysing a map they can acquire spatial information that would help them locate the location that would help them thrive and outwit the other competitors. Many factors would affect the positioning of their establishment. This study will help them as the objectives of the study are to create a map of fast food establishment in Kota Bharu and to determine the factors that is involved in the placement of a fast food establishment.